2010
DOI: 10.19030/iber.v9i10.634
|View full text |Cite
|
Sign up to set email alerts
|

Motives For Employee Profit Sharing Schemes In The U.S., U.K. And Canada

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 26 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…Another type of agricultural financing is profit sharing among the stakeholders involved in the agricultural activities with several motives such as labor productivity, cost monitoring, and wage flexibility (Daneshfar et al, 2010). Labor productivity is achieved through higher employees motivation and involvement whereas monitoring system occurs because the employees could observe the actions of other employees.…”
Section: Research Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Another type of agricultural financing is profit sharing among the stakeholders involved in the agricultural activities with several motives such as labor productivity, cost monitoring, and wage flexibility (Daneshfar et al, 2010). Labor productivity is achieved through higher employees motivation and involvement whereas monitoring system occurs because the employees could observe the actions of other employees.…”
Section: Research Frameworkmentioning
confidence: 99%
“…Figure 3 illustrates the structure of mudarabah Sukuk. In line with Daneshfar et al (2010) and Dusuki (2010), a profit sharing arrangement is proposed for the agricultural development in the research area as can be seen in Figure 4. The investor and the farmers/land-owners signed an agreement to utilize investor's fund for the agricultural development.…”
Section: Research Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…• United States: Profit-sharing schemes, on a voluntary basis, take on several forms in the United States: (i) the cash plan, under which contributions are paid directly to employees in the form of cash or stock; (ii) the deferred plan, which works as a supplementary insurance plan, so the share that the company credits to the plan can be made effective at the retirement, disability, death, etc. of the employee; (iii) and the combination plan, under which the employee can defer all or part of the profit-sharing allocation as in the deferred plan or can use it in cash (Daneshfar et al, 2010).…”
Section: … and A More Equal Distribution Of The Gainsmentioning
confidence: 99%
“…• Moreover, profit sharing could reduce firms' monitoring costs through the generation of peer pressure. Studies have shown that where there is a profit-sharing scheme, employees have an incentive to observe the actions of their peers because the behaviour of each employee has an impact on the output of the company and, therefore, on the earnings of the rest of the employees (Daneshfar et al ., 2010;Kandel and Lazear, 1992).…”
Section: … and A More Equal Distribution Of The Gainsmentioning
confidence: 99%